Enzyme kinetic approach for mechanistic insight and predictions of in vivo starch digestibility and the glycaemic index of foods. (February 2022) - Butterworth, Peter J.; Bajka, Balázs H.; Edwards, Cathrina H.; Warren, Frederick J.; Ellis, Peter R.
Abstract: Background: Starch is a principal dietary source of digestible carbohydrate and energy. Glycaemic and insulinaemic responses to foods containing starch vary considerably and glucose responses to starchy foods are often described by the glycaemic index (GI) and/or glycaemic load (GL). Low GI/GL foods are beneficial in the management of cardiometabolic disorders (e.g., type 2 diabetes, cardiovascular disease). Differences in rates and extents of digestion of starch-containing foods will affect postprandial glycaemia. Scope and approach: Amylolysis kinetics are influenced by structural properties of the food matrix and of starch itself. Native (raw) semi-crystalline starch is digested slowly but hydrothermal processing (cooking) gelatinises the starch and greatly increases its digestibility. In plants, starch granules are contained within cells and intact cell walls can limit accessibility of water and digestive enzymes hindering gelatinisation and digestibility. In vitro studies of starch digestion by α-amylase model early stages in digestion and can suggest likely rates of digestion in vivo and expected glycaemic responses. Reports that metabolic responses to dietary starch are influenced by α-amylase gene copy number, heightens interest in amylolysis. Key findings and conclusions: This review shows how enzyme kinetic strategies can provide explanations for differences in digestion rate of different starchy foods. Michaelis-Menten and Log of Slope analyses provide kinetic parameters (e.g., K m and k cat /K m ) for evaluating catalytic efficiency and ease of digestibility of starch by α-amylase. Suitable kinetic methods maximise the information that can be obtained from in vitro work for predictions of starch digestion and glycaemic responses in vivo . Graphical abstract: Image 1 Highlights: Michaelis-Menten kinetics determines catalytic efficiency of amylase action on starch. Kinetic parameters K m and k cat /K m are useful for estimating ease of digestibility. Log of slope analysis can quantify starch fractions digested at different rates. Categorisation of Resistant Starch can be based on types of interaction with amylase. Enzyme kinetic studies of amylolysis are useful for predicting postprandial glycaemia.